(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
1U. of K. J. Agric. Sci. 22(1), 1-12, 2014Mathematical Models of Moisture Sorption Isotherms of GrainsSorghum (Sorghum bicolor (L.) Moench)Eman Abdu Abdalla1 , Mohamed Ayoub Ismail and AbdelmoniemElamin Mohamed2Department of Agricultural Engineering, Faculty of Agriculture,University of Khartoum, SudanAbstract: The objective of the study was to fit or test the experimentaldata of adsorption and desorption isotherms of grains sorghum The studywas carried out at the Department of Agricultural Engineering, Faculty ofAgriculture, University of Khartoum and the Food Processing ResearchCenter, Shambat, Sudan, during January 2007 - March 2008. Fourmathematical models namely modified Henderson, modified Chung-Pfost, modified Oswin and modified Halsey were used to predict sorptionisotherms. The adsorption and desorption isotherms were determinedusing standard static gravimetric method, six levels of water activitiesrang 0.112- 0.865 were maintained by using saturated salt solutions insideair-tight glass desiccators, while incubators were used to maintain three aconstant temperature namely 25oC,35 oC and 45oC. A non-linearregression analysis was used to evaluate the parameters of the fourselected models. The models were compared by using statisticalparameters: mean relative percentage deviation (P%), standard error ofestimates (Es), coefficient of determination (R2 ) and randomness ofresidual plots of difference between measured and predicted values. Forthe mathematical models, the results indicated that the modified Chung-Pfost model satisfactorily predicts the adsorption and desorptionisotherms of grains sorghum